ANTIBACTERIAL ACTIVITY TEST OF ETHANOL EXTRACT 70% OF FALOAK BARK (Sterculia quadrifida R.Br) ON Klebsiella Pneumoniae BACTERIA - Shita Anggenella Dupe; Rr. Listyawati Nurina; Efrisca M. Br Damanik; Prisca Deviani Pakan (Cendana Medical Journal, 2025)
Introduction: Pneumonia is a common lower respiratory infection affecting all ages, caused by bacteria, viruses, fungi, or parasites. Klebsiella pneumoniae is a bacterial cause showing high antibiotic resistance, complicating treatment. As a result, alternative treatments using medicinal plants with antibacterial properties are needed. One promising plant is faloak (Sterculia quadrifida R.Br), traditionally used in herbal medicine and believed to have potential antibacterial effects worth further investigation. Methods: This study employed a true experimental method with a post-test only control group design. The treatment groups were given 70% ethanol extract of faloak bark at various concentrations (100%, 50%, 25%, 12.5%, 6.25%, and 3.12%). There were also a positive control group (meropenem antibiotic) and a negative control group (sterile distilled water). Data were analyzed using the Kruskal-Wallis test. Results: The 70% ethanol extract of faloak bark showed antibacterial activity against Klebsiella pneumoniae, with a significance value of p = 0.002 (< 0.05), indicating a significant difference in the inhibition zone diameters. Discussion: The extract demonstrated antibacterial properties and the ability to inhibit the growth of Klebsiella pneumoniae. Conclusion: The 70% ethanol extract of faloak bark (Sterculia quadrifida R.Br) exhibits antibacterial activity against Klebsiella pneumoniae.